Effects of regular and fortified biochar on the yield and phenological properties of cucumber (cucumis sativus l.) under check basin irrigation - Sadiq, Yakubu; Lawatla, Hamza Shuaibu; Haruna, Yakubu Banyes; Ibrahim, Ahmad Kawu; Idris, Sani (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2024)
The effectiveness of normal biochar (NB) on the performance of cereal crops has been well studied. However, in the arid climate, such studies are deathly limited for garden crops. As such, a field experiment was conceived and executed during the 2023 dry season to determine the yield, and phenological responses of cucumber (Cucumis sativus L) to the application of NB and inorganically fortified biochar (FB). The experimental treatments consist of NB, FB, inorganic fertilizer (IF), and control (CT) assigned in a randomized complete block design and replicated three times. The NB was applied at 11 tonnes ha–1 equivalent rate, while plots under IF treatment received a standard rate of 130kgha–1 N, 95 P2O5 and 200 K2O kgha–1 equivalence using split application at 3 and 6 weeks after emergence. The test crop was seeded at 2kgha– 1. The yield outcome under FB (0.1277kgm– 2) outmatched those under NB, IF, and CT by 60, 42, and 77% respectively. Similarly, FB recorded a significantly greater number of leaves (12.0 per stand), and leaf area index (236.86cm2) compared to other treatments. Having produced better yield and biomass, FB treatment can be recommended for Guinea Savana soils of Nigeria under the check basin irrigation system.